Single‐cell profiling reveals distinct immune phenotypes that contribute to ischaemia‐reperfusion injury after steatotic liver transplantation. (1st September 2021) - Yang, Xinyu; Lu, Di; Wang, Rui; Lian, Zhengxing; Lin, Zuyuan; Zhuo, Jianyong; Chen, Hao; Yang, Modan; Tan, Winyen; Yang, Mengfan; Wei, Xuyong; Wei, Qiang; et al.
Abstract: Objectives: The discrepancy between supply and demand of organ has led to an increased utilization of steatotic liver for liver transplantation (LT). Hepatic steatosis, however, is a major risk factor for graft failure due to increased susceptibility to ischaemia‐reperfusion (I/R) injury during transplantation. Materials and methods: To assess the plasticity and phenotype of immune cells within the microenvironment of steatotic liver graft at single‐cell level, single‐cell RNA‐sequencing (scRNA‐Seq) was carried out on 23 675 cells from transplanted rat livers. Bioinformatic analyses and multiplex immunohistochemistry were performed to assess the functional properties, transcriptional regulation, phenotypic switching and cell‐cell interactions of different cell subtypes. Results: We have identified 11 different cell types in transplanted livers and found that the highly complex ecosystem was shaped by myeloid‐derived cell subsets that transit between different states and interact mutually. Notably, a pro‐inflammatory phenotype of Kupffer cells (KCs) with high expression of colony‐stimulating factor 3 (CSF3) that was enriched in transplanted steatotic livers was potentially participated in fatty graft injury. We have also detected a subset of dendritic cells (DCs) with highly expressing XCR1 that was correlated with CD8 + T cells, mediating the severer steatotic liver damage by I/R injury. Conclusions: The findings of our study provide new insight into the mechanisms by which steatosis exacerbates liver damage from I/R injury. Interventions based on these observations create opportunities in attenuating fatty liver graft injury and expanding the donor pool. Abstract : The schematic of workflow for the sample preparation, sequencing and bioinformatic analysis.